Girls think of everything : stories of ingenious inventions by women - Thimmesh, Catherine; Sweet, Melissa (Boston : Houghton Mifflin, 2000)
Tells the story of how women throughout the ages have responded to situations confronting them in daily life by inventing such items as correction fluid, space helmets, and disposable diapers.
Includes bibliographical references (p. 54-56) and index.
School Library Journal
Book Links (A.L.A.)
Booklist
6.0
3-6
Keywords: Women inventors -- United States -- Biography -- Juvenile literature; Inventions -- United States -- History -- Juvenile literature; Women inventors; Inventors; Inventions; Women -- Biography; Women inventors -- Biography; Inventors -- Biography; Inventions; Women -- Biography